Pengaruh Inovasi Layanan terhadap Kepuasan Pelanggan Garuda Indonesia di Bandar Udara International Yogyakarta - Dhea Vita Nataya; Kifni Yudianto (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The development of air transportation is growing rapidly in Indonesia, this makes the airport there are almost every city in Indonesia. In order to compete internationally, the company must always create new innovations to attract customers. One example is Garuda Indonesia. In addition to the top brand the airline has also received Operational Safety Audit (IOSA) certification, which means that Garuda has fully met international aviation safety standards. In this study, the authors used a quantitative approach. To borrow the term Cresweel (2010), which states quantitative approaches are measurements of quantitative data and objective statistics through scientific calculations derived from a sample of people or residents who were asked to answer a number of questions about the survey to determine the frequency and percentage of their responses. The results obtained by researchers in this study are, service innovation has a positive and significant effect on customer satisfaction it is evidenced by a significant value of 0.000 which is smaller than 0.05. While the effect of service innovation was 0.476 or 47.6% while the rest was influenced by other variables not studied in the study. Keywords: Service Innovation, Customer Satisfaction, Garuda Indonesia